The Debate on Brexit Defaming Globalisation by Constructing it on the Grounds of Nationalism (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This essay tries to examine that why on a very first place Brexit happened. Why people voted in the support of Brexit. After so many years of integration, UK decided to leave European Union. This paper explores, that the debate on Brexit includes more than the issue of sovereignty and national identity. The politics regarding the borders and economy and control over it was the main concern. It is not only Britain but European Union (EU) will be affected mostly by the Brexit. The Brexit has left a space in EU questioning its ideology based on globalisation which bind the international stage in a cooperative and dependable matters on the issue of security, terrorism and power